A Framework for Developing Collaborative Case Tools - Swee Sin, Kevin Soon; Palaniappan, Sellapan (Malaysian Journal of Computer Science, 2005)
This paper proposes a light-weight framework called LICOSE (LIghtweight COllaborative SErvices) that is suitable to execute Java programs on a client that has constraint-limited environment such as Java Runtime Environment (JRE) for applets and Personal Digital Assistants (PDAs). This framework also allows high-level calls to be made to leverage the underlying publish/subscribe mechanism provided by the Java Message Services (JMS). Although socket connections are created and managed behind-the-scenes, the distributed collaborative application developer need not worry about the internal plumbing involved. This framework thus acts as both a FaÃ§ade (for simplifying the intricate JMS interfaces) and a Proxy (for providing a surrogate interfaces for developers to invoke upon). A prototype CASE tool with collaborative features is developed using this framework.